Country image of Finland : The experiences of international students - Puustinen, Aino (My University, 2024)
International students hold great potential for contributing to Finland’s growing need of skilled workers. Therefore, attracting and retaining these students is of high importance. Country images, as subjective attitudes among foreign publics, offer a theoretical lens for studying international students’ experiences and attitudes. Moreover, there is a research gap on the country image of Finland from the perspective of international students. Therefore, the aim of this study was to explore how international students experience the country image of Finland. Country image consists of beliefs (cognitions) and emotions (affects), which influence behavioural intentions (conations). Country image influences international students’ destination country choices as a halo construct. When an individual has experience of a country, country image as a summary construct combines these experiences. This is consistent with literature on international students’ post-graduation intentions, and therefore, country image is expected to influence post-graduation intentions through experiential knowledge. Personal values and experiences affect the formation of the overall evaluation through cognitions, while cultural intelligence and integration to the host country affect the interpretation of firsthand experiences. This study was conducted as qualitative research with an interpretative approach. The data was gathered by interviewing international degree-students and graduates in Finland and analysed thematically. The five themes emerged from the data and aimed for interpreting the central phenomena connected to the aim of the study as wholes. The themes discussed the role of information in choosing a destination country, living quality in comparison to home countries, dealing with cultural differences, the roles of job search and politics in creating uncertainty, and the students’ post-graduation intentions. This study supports previous research by arguing that country image can influence international students’ destination country choices as a halo construct significantly, and, to an extent, post-graduation intentions as a summary construct. The students’ high motivation to look for information before choosing a destination country was also consistent with previous studies. Living quality was the most important aspect of Finland’s country image, which emphasizes how students interpret country cognitions into affects according to their own personal background. On the other hand, difficulties in finding employment and tightening immigration policies had created feelings of not being welcome and lowered equality perceptions. Cultural intelligence and personal motivation may help with integration and in the formation of a positive country image. The findings of this study suggest that to attract and retain students who are dedicated to stay in the country, it is important for Finland to hold on to high living quality factors, such as safety, and family well-being. The effect of positive word-of-mouth could possibly be grown by enhancing international students’ experiences. It is suggested that policymakers and employers could work together to improve international students’ working opportunities. Moreover, it seems that policymakers could re-evaluate some of the tighter immigration policies and consider what type of message they send to international students.

Osaavan työvoiman tarve kasvaa Suomessa. Yksi ratkaisu on houkutella kansainvälisiä opiskelijoita ja etsiä keinoja, joilla heidät saadaan jäämään tänne. Maakuva on ulkomaalaisten subjektiiviset asenteet maata kohtaan, joten se tarjoaa teoreettisen kulman tutkia kansainvälisten opiskelijoiden asenteita ja kokemuksia. Suomen maakuvaa ei ole aikaisemmin tutkittu kansainvälisten opiskelijoiden näkökulmasta. Tämän vuoksi tämän pro gradu -tutkimuksen tavoitteena on selvittää, miten kansainväliset opiskelijat kokevat Suomen maakuvan. Maakuva koostuu uskomuksista (kognitiot) ja tunteista, jotka vaikuttavat käyttäytymisaikomuksiin. Maakuva vaikuttaa kansainvälisten opiskelijoiden kohdemaan valintaan sädekehäkonstruktiona (halo construct). Siinä vaiheessa, kun opiskelijalla on kokemusta kohdemaasta, maakuva tuo nämä kokemukset yhteen. Maakuva yhteen vetävänä konstruktiona (summary construct) on linjassa kansainvälisten opiskelijoiden valmistumisen jälkeisiä aikomuksia käsittelevän tutkimuksen kanssa, joten odotus on, että maakuva vaikuttaa opiskelijoiden aikeisiin jäädä Suomeen kokemustiedon kautta. Henkilökohtaiset arvot ja kokemukset vaikuttavat tunteiden muodostumiseen kognitioiden kautta. Toisaalta kulttuurinen älykkyys (cultural intelligence) ja yksilön integraatio kohdemaahan vaikuttavat siihen, miten opiskelijat tulkitsevat kokemuksiaan. Tutkimus toteutettiin laadullisena, ja lähestymistapana on interpretivismi. Data kerättiin haastattelemalla Suomessa opiskelevia kansainvälisiä tutkinto-opiskelijoita Suomessa, sekä jo valmistuneita. Data analysoitiin temaattisesti. Muodostetut viisi teemaa käsittelevät tiedon roolia kohdemaan valinnassa, elämänlaatua verrattuna kunkin kotimaahan, kulttuurieroja, työnhaun ja politiikan vaikutusta epävarmuuteen sekä aikomuksia jäädä Suomeen. Tämän tutkimuksen johtopäätökset tukevat aikaisempaa kirjallisuutta osoittamalla, että maakuva voi vaikuttaa merkittävästi kansainvälisten opiskelijoiden kohdemaan valintaan sädekehäkonstruktiona ja jossain määrin valmistumisen jälkeisiin aikomuksiin yhteen vetävänä konstruktiona. Kansainvälisten opiskelijoiden korkea motivaatio etsiä tietoa kohdemaasta ennen opiskelumaan valintaa on linjassa aikaisemman kirjallisuuden kanssa. Elämänlaatu on maakuvan tärkein osa-alue, mikä korostaa sitä, miten opiskelijat tulkitsevat uskomuksia tunteiksi oman, henkilökohtaisen taustansa mukaan. Toisaalta työnhakuun liittyvät haasteet ja maahanmuuttopolitiikan kiristyminen ovat aiheuttaneet opiskelijoille tunteita siitä, etteivät he ole tervetulleita ja heikentäneet käsityksiä tasa-arvosta Suomessa. Kulttuurinen älykkyys ja henkilökohtainen motivaatio saattavat puolestaan edistää integraatiota ja parantaa maakuvaa. Tutkimuksen tulosten perusteella ehdotan, että Suomen kannattaa pitää tiukasti kiinni hyvän elämän perusperiaatteita, kuten turvallisuudesta ja perheiden hyvinvoinnista. Niiden avulla voidaan houkutella Suomeen sitoutuneita kansainvälisiä opiskelijoita ja edistää heidän jäämistään maahan. Opiskelijoiden kokemuksia parantamalla on mahdollista lisätä myönteistä suullisesti leviävää tietoa (word-of-mouth). Suosituksena on, että päättäjät ja työnantajat tekevät yhteistyötä parantaakseen kansainvälisten opiskelijoiden työllistymistä. Tämän tutkimuksen perusteella vaikuttaa siltä, että joitain maahanmuuttopolitiikan tiukennuksia kannattaa harkita uudelleen. Olennaista on miettiä, minkälaisen viestin ne antavat kansainvälisille opiskelijoille ja muulle osaavalle työvoimalle.
Keywords: Country image, international students, Finland, destination country, post-graduation intentions, country image changes, politics, maakuva, kansainväliset opiskelijat, Suomi, opiskelumaan valinta, valmistumisen jälkeiset aikomukset, maakuvan muuttuminen, politiikka